Intraspinal bleeding in haemophilia: successful treatment with factor VIII concentrate. Issue 12 (December 1977) - Harvie, A; Lowe, G D; Forbes, C D; Prentice, C R; Turner, J
Abstract : A severely affected haemophilic boy became tetraparetic as a result of a spontaneously occurring intraspinal haematoma. Myelography defined the extent of the lesion and showed it to be extradural in site. Infusion of large doses of factor VIII concentrate led to dramatic improvement and avoided the need to operate.